Delayed Return: Consolidation of the Zimbabwean Diaspora and Transnationalism - Jaji, Rose (2021)
This article discusses consolidation of the Zimbabwean diaspora and its transnational activities. It presents formation of this particular diaspora as an unanticipated development that is contingent upon circumstances as they evolve in both sending and receiving countries. It draws from longitudinal research with Zimbabwean migrants in Germany and South Africa to illustrate this argument. It also borrows from Tsuda’s transnational outcome framework to provide a nuanced understanding of Zimbabwean migrants’ varied relationships with both Zimbabwe and the receiving countries. The article argues that migrants’ decision to settle for the long-term in the receiving country is not always made at the same time as the decision to migrate itself or in the initial stages of life in the receiving country. There are many cases among Zimbabwean migrants showing that migration was initially perceived as quest for reprieve from the country’s economic and political challenges while they “waited” for the situation to...